Optimalisasi Waktu dan Biaya dengan Penambahan Jam Kerja Lembur 3 Jam dan Shift Kerja - Sudianto, Toto; Mahendra, Muhammad Oka; Putra, Al Fiillian Sah; Qishas, Haechal Fachar (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
In construction projects, delays often occur, causing increased costs and delays in completion. This study analyzes project acceleration with the crashing method on the Untirta Rectorate Building Construction Project, comparing the alternatives of 3-hour overtime and work Shifts. The goal is to determine the optimal project duration and cost. The analysis shows that there are 14 jobs on the critical path. The results of acceleration with 3-hour overtime resulted in a project cost of Rp3,104,007,500 with a duration of 431 days, while work Shifts require Rp1,280,228,250 with a duration of 427 days. The total slope cost for 3-hour overtime is Rp193,244,923.38, and work Shifts Rp36,611,338.93. Alternative cost comparison shows that overtime has direct costs of Rp49,158,386,780 and indirect costs of Rp3,971,376,850, while Shift work has direct costs of Rp47,334,607,530 and indirect costs of Rp3,962,700,980. Shift work is more efficient in terms of cost and time.